The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4025/cienccuidsaude.v10i2.10254
|View full text |Cite
|
Sign up to set email alerts
|

Produção do conhecimento em enfermagem: contribuição de um curso de mestrado

Abstract: RESUMOAo longo dos últimos dez anos o curso de mestrado em enfermagem da Universidade Federal de Santa Catarina (UFSC) produziu muitas dissertações, produção que faz necessário conhecer de modo sistematizado, como um importante passo para o processo de avaliação do curso. O presente estudo identifica-se como uma pesquisa descritiva de abordagem quantitativa e consiste em uma análise documental das 195 dissertações defendidas no Curso de Mestrado da UFSC no período de janeiro de 1999 a janeiro de 2004. Para o r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study from the CNPq investments to support research in Nursing found that there are large gaps to be filled in the field of Nursing, which require policies that motivates researchers to search for opportunities, challenges and possibilities. A political agenda focused on research is needed to promote joint actions of leadership together with the Universities and representatives in the field of Nursing to conduct nursing research coherent with the real needs experienced by our profession in the Brazilian healthcare scenario (18) .…”
Section: Graduate Program In Nursing At the Federal University Of Sanmentioning
confidence: 99%
“…A study from the CNPq investments to support research in Nursing found that there are large gaps to be filled in the field of Nursing, which require policies that motivates researchers to search for opportunities, challenges and possibilities. A political agenda focused on research is needed to promote joint actions of leadership together with the Universities and representatives in the field of Nursing to conduct nursing research coherent with the real needs experienced by our profession in the Brazilian healthcare scenario (18) .…”
Section: Graduate Program In Nursing At the Federal University Of Sanmentioning
confidence: 99%